HUBUNGAN BEBAN KERJA, POSTUR DAN DURASI JAM KERJA DENGAN KELUHAN NYERI LEHER PADA PORTER DI PELABUHAN PENYEBERANGAN FERRY MERAK-BANTEN - Setyowati Setyowati; Baju Widjasena; Siswi Jayanti (Jurnal Kesehatan Masyarakat (Undip), 2017)
Porter's activity of manually carrying goods by putting them on their shoulders may cause burden and unnatural posture of the neck bone so it may affect pain in neck. The purpose of this research is to acknowledge the correlation between work load, load weight, work posture, flexing posture, weight lifting duration, and working duration with neck pain on porters at Merak Ferry Port Banten. This observational study is conducted in cross-sectional approach. Population in this study are porters of Merak Ferry Port Banten in number of 64 persons. The sampling method uses total population sampling with criterias. Correlation analysis uses Rank Spearman correlation test. Based on the results, it was found that variables related to neck pain complaints were work load (p-value  = 0,031), handling posture (p-value = 0,018), and work duration (p-value = 0,047). Variables unrelated to neck pain were load weight (p-value = 0,144), lifting posture (p-value = 0,774), lifting duration (p-value = 0,144), and flexing posture (p-value = 0,974). It is necessary to implement working hour policy of 8 hours a day with maximum overtime of 3 hours as well as health service assistance from local health center. Porters should apply the correct manual handling positions.